Do you do what you say or do you do what you say others do? - Fredrik Carlsson; Dinky Daruvala; Henrik Jaldell (Journal of Choice Modelling, 2010)
We design a donations vs. own money choice experiment and compare the results from three different treatments. In two of the treatments the pay-offs are hypothetical. In the first of these, a short cheap talk script was used and subjects were required to state their own preferences in this scenario. In the second treatment, subjects were asked to state how they believed the average student would respond to the choices. In the third treatment the pay-offs were real, allowing us to use the results to compare the validity of the two hypothetical treatments. Our hypothesis is that when subjects are asked to state how they believe an average person would respond, they will use their own preferences in their responses without using the survey situation for self-enhancement. However, we find a large difference in the results from both hypothetical treatments compared to the real money treatment. We find that the marginal willingness to pay for donations is higher when subjects state their own preferences but lower when subjects state what they believe are other people's preferences. We also find that it is mainly women who are prone to these differences in the study.
Keywords: 330; stated preferences; cheap talk; third person approach; choice experiment